Predatory aggression evolved through adaptations to noradrenergic circuits - Güniz Göze Eren; Leonard Böger; Marianne Roca; Fumie Hiramatsu; Jun Liu; Luis Alvarez; Desiree L. Goetting; Lewis A. Cockram; Nurit Zorn; Ziduan Han; Misako Okumura; Monika Scholz; et al. (Nature, 2026)
Abstract Behaviours are adaptive traits evolving through natural selection. Crucially, the genetic, molecular and neural modifications that shape behavioural innovations are poorly understood 1 . Here, we identify specialized adaptations linked to the evolution of invertebrate aggression 2 . Using the predatory nematode Pristionchus pacificus , we developed a machine learning model from behavioural tracking data and identified robust behavioural states associated with aggressive episodes. Strikingly, predatory aggression coincides with a rewiring of key circuits across nematode evolution. We find modifications to the noradrenergic pathway, with octopamine promoting aggressive predatory bouts whereas tyramine antagonistically induces passive states. Modulation occurs through the octopamine receptors Ppa-ser-3 and Ppa-ser-6 , and tyramine receptor Ppa-lgc-55 . These localize to sensory neurons whose inhibition diminishes aggressive events. Crucially, this octopaminergic innovation emerged within this predatory lineage, consistent with an ancient divergence in function. Thus, evolutionary adaptations in noradrenergic circuits facilitated the emergence of aggressive behavioural states associated with complex predatory traits.